A case study of an early Islamic city in Transoxiana: Excavations at the medieval citadel in Taraz, Kazakhstan. (December 2015) - Dawkes, Giles; Jorayev, Gaygysyz
Abstract: This report presents a summary of the 2011 and 2012 excavations of the joint UK–Kazakhstani excavations in the medieval citadel of Taraz. The city of Taraz, located near the southern border with Uzbekistan, is one of the most significant historic settlements in Kazakhstan, and the investigations in the central market place have started to reveal the composition of the medieval city. Despite frequent mentions in Arabic and Chinese written sources, the form and evolution of this important Silk Road city remains poorly understood. These excavations, which identified a series of buildings including a bathhouse and a fire shrine, are the first for almost 50 years and include the first C 14 radiocarbon date from the city. In addition, this is one of the first detailed accounts in English of an urban excavation in Kazakhstan.